Perlindungan Hukum Terhadap Pelanggar Privasi Konsumen Dalam Jual Beli Online - Komang Pande Angga Tridipta; I Nyoman Sujana; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—Electronic media is one of container to communicate also to do a business with way to use it internet media. To through internet media some types act criminal easy be done. Technology also it’s attend internet be seen from corner view economy can to easier us in to do economy activity. While if seen from corner view law technology also with it’s attend this internet can become indication it’s appear phenomenon the law that can caused its emerge the criminal act new. Research with title Law Protection In Breaker Consumer's Privacy online trading to own formula of How problem Law Protection In Infringement Consumer's Privacy in online trading and does Solution Quarrel In Privacy's Infringement Consumer online trading. This research to use it research Type method and problem approach, Law Material Source, the Technique of law material-collection, and Law Material Analytical. Decomposing To be based and the research result discussion that be done so can be pulled conclusion that activity sold buy online has difference with transaction sell buy conventionally. Form law protection in infringement consumer's privacy in selling transaction buy online to be explained as law problems in transaction scope online trading that is Privacy, Subject's Authority Law and Object Transaction e-commerce. Quarreling solution in privacy's infringement consumer online trading be done with litigation (justice).